The Epistemic Fault Line in Corporate Governance - Donaldson, Thomas (Academy of Management Review, 2012)
An epistemic fault line separating positive from normative concepts underlies theories of corporate governance. I analyze this fault line in order to show the importance of clarifying normative assumptions in governance models. I formulate an impossibility theorem for corporate governance that demonstrates how contemporary theories neglect normative concepts. Applying the theorem clears the way both for the better use of existing models and for the design of more epistemologically sophisticated models.